Late Quaternary fluvial terrace characteristics and ages of the Pamir‒Tian Shan convergence zone: indications of regional climate change and tectonic uplift - Deng, Jinhua; Li, Tao; Feng, Jiahui; Qian, Li (Frontiers in Earth Science, 2024)
The Pamir‒Tian Shan collision zone, located at the northwestern edge of the Himalaya‒Qingzang orogenic belt, provides a natural laboratory for investigating the development of fluvial terraces controlled by regional climate change and tectonic uplift. In this study, we conducted geomorphological mapping and terrestrial cosmogenic nuclide 10Be dating of fluvial terraces in the Wuheshalu syncline, within the Pamir‒Tian Shan collision zone. Four major fluvial terraces were identified in the Wuheshalu syncline, with ages of approximately 187, 141, 90, and 19 ka, respectively. These terraces were abandoned during three glacial‒interglacial transition periods (Marine Isotope Stage 6/5 (MIS6/5), cold-to-warm transition period of MIS5, and end of MIS2 or MIS2/1) and one interglacial‒glacial period (MIS7/6), and exhibit a strong correlation with regional climate change. Tectonic uplift contributed only one-third of the observed fluvial incision. These results suggest that river incision and terrace formation in the Pamir‒Tian Shan collision zone are primarily driven by periodic fluctuations in climate, with a lesser contribution from tectonic uplift.